Paradoks Globalisasi Sebagai Tegangan Abadi Universalisme Dan Relativisme Budaya Hak Asasi Manusia dalam Prespektif Antropologi - , Luna Brillyant Ensebu, Dina Fitra Amalia (PARENTAL, 2014)
Abstract The application of human rights on a national scale, namely universalism and cultural relativism. On the one hand, universalism stated that there will be more culturally "primitive" that eventually evolved to the legal system and then have the same rights with Western culture. Cultural relativism on the other hand, say the opposite, namely that of a traditional culture can not be changed. Along with the advent of globalization is the spread of values, concepts, and laws from around the world to various parts of the world. Finally, globalization produces the paradox that one of the reasons the tensions between universalism and cultural relativism. Starting from the basic words of human rights in the minds of the followers of universalism as overcoming dimensions of space and time and then got skepticism by cultural relativists against improper human words with human words related to the complexity of the cultural uniqueness of the local culture which is the study of anthropology . Thus the authors will try to present Eternal Paradox of Globalization as Universalism and Relativism Voltage Cultural Dimensions of Human Rights in Anthropology. Keywords: Human Rights, Universalism, Cultural Relativism, Globalization Paradox, Anrtopologi